COVID-19 aus Sicht des Nephrologen - Kann, Martin; Benzing, Thomas (DMW - Deutsche Medizinische Wochenschrift, 2020)
Increasing insight into the clinical phenotype and mechanisms of SARS-CoV-2 infections and COVID-19 has identified damage of the kidneys as a key player in the course of the disease. This manuscript summarizes the current knowledge on direct viral infection of kidney tissue, proteinuria and acute kidney injury in COVID-19, and management of patients on chronic dialysis as well as after kidney transplantation. Direct infection of podocytes and proximal tubular cells by SARS-CoV-2 has been confirmed and results in proteinuria and hematuria at an early stage of COVID-19. In this context, any kidney affection is a predictor of worse outcomes among COVID-19 patients irrespective of the initial presentation and increases the risk of acute kidney injury. Specific therapies for kidney damage and acute kidney injury within COVID-19 that could be generally recommended are currently lacking. Patients on chronic hemodialysis in particular are at risk for contracting SARS-CoV-2 infections as indicated by outbreaks and super-spreading events in hemodialysis facilities. Immunosuppressive therapy after kidney transplantation needs to be adapted upon diagnosis of COVID-19 depending on the severity of the initial presentation.
Keywords: Nierenbeteiligung; akutes Nierenversagen; Dialysetherapie; Transplantation; SARS-CoV-2